CULTURAL FACTORS ASSOCIATED WITH IRON DEFICIENCY ANAEMIA IN PREGNANCY: A CASE STUDY OF THE KALUTARA DISTRICT, SRI LANKA (Proceedings of the Global Public Health Conference, 2019)
Anaemia is a global public health problem that affects the social and economic development of a country. The objective of this study is to identify the cultural factors associated with iron deficiency anaemia in pregnancy. The study is largely qualitative and consisted of thirty anaemic mothers each; from urban, rural and estate sectors of the Kalutara district. The study revealed a connection between cultural factors and anaemia. Most anaemic mothers had refrained from contraceptives and meat due to religious principles. They believed that meat is considered as an evil food. Some had the belief that anaemia could be eliminated by traditional spiritual beliefs such as pooja and thovil. Such myths have refrained them from taking the iron supplement. The burden of iron deficiency could be eliminated by iron fortification programs, media awareness, improving the life style and education, support from the health sector and employing Tamil speaking PHMs.
Keywords: anemia; health; culture; pregnancy